ANALISIS PARTISIPASI GURU DALAM WORKSHOP KURIKULUM DAN EFEKTIVITAS PEMBELAJARAN DI SMK KANSAI PEKANBARU - Defriona, Berlian; Fitriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze teachers’ participation in curriculum workshops and the effectiveness of learning at SMK Kansai Pekanbaru. The research applied a descriptive approach using questionnaires, interviews, observations, and documentation. The findings show that teachers’ participation is categorized as very good with an average score of 3.43, reflected in active involvement in discussions, lesson plan development, and reflection. Learning effectiveness is also categorized as very good with an average score of 3.37, indicated by more engaging, student- centered learning and the use of technology-based media. Teachers who have not attended workshops rely on other sources for curriculum understanding, though less comprehensively. Overall, there is a strong relationship between teachers’ participation in workshops and improved learning effectiveness